Association Study of Genetic Variants in Autophagy Pathway and Risk of Non-syndromic Cleft Lip With or Without Cleft Palate - Lou, Shu; Ma, Lan; Kan, Shiyi; Yu, Xin; Wang, Yuting; Yang, Fan; Zhu, Guirong; Fan, Liwen; Li, Dandan; Wang, Hua; Wang, Wei; Zhang, Weibing; et al. (Frontiers in Cell and Developmental Biology, 2020)
Although genetic variants in autophagy pathway genes were associated with the risk of oral cancers and early development in embryos, their associations with nonsyndromic cleft lip with or without cleft palate (NSCL/P) risk remained unclear. A two-stage case-control study (2,027 NSCL/P cases and 1,843 controls) was performed to investigate the associations between single nucleotide polymorphisms (SNPs) in 23 autophagy pathway genes and NSCL/P susceptibility. The logistic regression model was used to calculate effects of SNPs on NSCL/P susceptibility. Gene-based analysis was performed via the sequence kernel association test (SKAT) and multi-marker analysis of genomic annotation (MAGMA) methods. Expression quantitative trait loci (eQTL) analysis was conducted using NSCL/P lip tissue samples. Gene expression during embryonic development was evaluated using RNA-Seq. Functional roles were explored by luciferase activity assay, cell apoptosis, proliferation, and cycle in vitro. Rs2301104 in HIF1A was significantly associated with NSCL/P susceptibility in the combined analysis (OR=1.29, 95% CI=1.09-1.29, P=3.39E-03), and showed strong evidence of association heterogeneity (P=9.06E-03) with obvious association in the female (OR: 1.80; 95% CI: 1.32-2.45; P=1.79E-04). The G allele of rs2301104 was associated with enhanced transcription activity and high expression of HIF1A compared with that of C allele. Moreover, rs2301104 exhibited an eQTL effect for HIF1A with its GC/CC genotypes associated with decreased HIF1A expression compared with those with GG genotypes (P=3.1E−02). Knockdown of HIF1A induced cell apoptosis and inhibited cell proliferation in human embryonic palate mesenchyme (HEPM) and human oral epithelium cells (HOEC). This study demonstrated that rs2301104 in autophagy pathway gene HIF1A was associated with susceptibility of NSCL/P.